PENGARUH DEVIDEN PAYOUT RATIO, TINGKAT SUKU BUNGA BI, PROFITABILITAS (NPM), DAN LABA BERSIH TERHADAP HARGA SAHAM PADAPERUSAHAN MANUFAKTUR SEKTORI INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2016 - R. Novitasari Situmorang; Yosef Sigalingging; Heny Butar Butar; Evi Evi; Bayu Wulandari (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of investing investors is to get a return in the form of dividends while the company expects continuous growth for the survival of the company and strives to provide prosperity for the shareholders. This study aims to see the effect of dividend payout ratio, BI interest rates, profitability (NPM ), and net profit on stock prices in manufacturing companies in the consumer goods industry sector that are listed on the Indonesian stock exchange for the period 2012-2016. Determination of the sample uses purposive sampling method and the samples studied are 14 methods of data analysis using multiple regression analysis.